Transition amplitudes for the nonmesonic hypernuclear decay - Galeao, A. P. (American Institute of Physics (AIP), 2004)
We give general expressions for the two-body decomposition of the transition amplitudes for the nonmesonic decay of Lambda-hypernuclei within a finite-nucleus shell-model approach.